Implementasi Experiental marketing dalam menciptakan customer satisfaction dan repeat buying - Moh Idil Gufron; Amirotil Ummah (KITABAH: Jurnal Akuntansi dan Keuangan Syariah, 2020)
This research presents the urgency of implementing market experience as a creator of consumer satisfaction. The implication, it provides guidelines for consumers to choose to love the products offered by producers. This research uses descriptive qualitative library research approach. The data collection technique used was a referential analysis technique. In connection with this matter, this study examines the titles written with literature or theory studies whose sources are taken from books related to the titles being reviewed at this time which then obtain the results that have been written. The purpose of this study is to analyze the current market development in the economic view, as well as to increase the economic value in an area because this determines the level of regional progress. The results of this study indicate that experiential marketing is to improve people’s welfare. One example is to create customer satisfaction and make it a permanent customer or repeat buying.